“Bad Romance”: Links between Psychological and Physical Aggression and Relationship Functioning in Adolescent Couples - Inge Seiffge-Krenke (Behavioral Sciences, 2015)
Assortative mating is an important issue in explaining antisocial, aggressive behavior. It is yet unclear, whether the similarity paradigm fully explains frequent displays of aggression in adolescents’ romantic relationships. In a sample of 194 romantic partner dyads, differences between female and male partners’ reports of aggression (psychological and physical) and different measures of relationship functioning (e.g., jealousy, conflicts, and the affiliative and romantic quality of the relationship) were assessed. A hierarchical cluster analysis identified five distinct subgroups of dyads based on male and female reports of psychological and physical aggression: nonaggressive couples, couples with higher perceived aggressiveness (both physical and psychological) by females, couples with higher aggressiveness perceived by males and mutually aggressive couples. A substantial number of non-aggressive dyads emerged. Of note was the high number of females showing one-sided aggression, which was, however, not countered by their partner. The mutually aggressive couples showed the least adaptive relationship functioning, with a lack of supportive, trusting relationship qualities, high conflict rates and high jealousy. The discussion focuses on the different functions of aggression in these early romantic relations, and the aggravating impact of mutual aggression on relationship functioning and its potential antisocial outcomes.